2019
DOI: 10.1177/1745691619858402
|View full text |Cite
|
Sign up to set email alerts
|

Animals Have No Language, and Humans Are Animals Too

Abstract: Language is a cornerstone of human culture, yet the evolution of this cognitive-demanding ability is shrouded in mystery. Studying how different species demonstrate this trait can provide clues for its evolutionary route. Indeed, recent decades saw ample scientific attempts to compare human speech, the prominent behavioral manifestation of language, with other animals’ vocalizations. Diligent studies have found only elementary parallels to speech in other animals, fortifying the belief that language is uniquel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 66 publications
0
17
0
1
Order By: Relevance
“…One can find differences and draw parallels among the various human and nonhuman systems; doing so helps to delineate their various characteristics. The problem with doing so is that humans – despite all of our detailed work in the field for decades – are still fairly incompetent in their ability to perform complete analyses of any systems other than their own, so that additional complexities in nonhumans’ systems – and thus possible additional differences and parallels with the human system – currently remain undiscovered, particularly with respect to reference (see Prat, 2019 ). For example, when birdsongs that are recorded at normal speed are played back at much slower speeds, many small structural differences can be observed among supposedly identical elements, emitted from different songsters or even from the same individual.…”
Section: Discussionmentioning
confidence: 99%
“…One can find differences and draw parallels among the various human and nonhuman systems; doing so helps to delineate their various characteristics. The problem with doing so is that humans – despite all of our detailed work in the field for decades – are still fairly incompetent in their ability to perform complete analyses of any systems other than their own, so that additional complexities in nonhumans’ systems – and thus possible additional differences and parallels with the human system – currently remain undiscovered, particularly with respect to reference (see Prat, 2019 ). For example, when birdsongs that are recorded at normal speed are played back at much slower speeds, many small structural differences can be observed among supposedly identical elements, emitted from different songsters or even from the same individual.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly assumed that there is no equivalent to human language in other animal species. Identifying meaning in non-human animal communication is probably the most difficult task in linguistics because of our limited ability to infer the real goals and intentions of non-human animals (Prat, 2019). One problem with effective communication is that tests are conducted in the expectation that animals will perform in a similar way to humans (Lockwood, 1987).…”
Section: Verbal Argumentsmentioning
confidence: 99%
“…One problem with effective communication is that tests are conducted in the expectation that animals will perform in a similar way to humans (Lockwood, 1987). In animal tests dealing with auditory communication, Prat (2019) considered it bothersome that humans in tests are assumed to be unique and superior, while studies of nonhuman animals' vocal communication provided results like those expected if similar methods were to be applied to human vocal behaviour. Human communication centres on vocal and visual means.…”
Section: Verbal Argumentsmentioning
confidence: 99%
“…These calls can be combined into a pyow-hack sequence, which elicit a group movement in receivers in the absence of predators: the meaning of this combination does not seem to be derived from the meaning of its constituents Moreover, playback experiments showed that listeners responded similarly to sequences in which the proportion of pyows and hacks varied, further suggesting that these combinations are non-compositional (but see Schlenker et al, 2016a for another interpretation of the data, discussed further in III.6). (Prat, 2019). This result is puzzling, and strongly suggests that, in order to properly compare animal and human communication and find linguistic-like capacities in animals, we should unify the methods.…”
Section: (B) Qualifying Syntactic Structuresmentioning
confidence: 99%
“…Moreover, the great differences between the methodologies that are possible in the two domains often make any direct comparison of results extremely challenging. In one striking example, Prat (2019) argues that, while ethological methodologies have thus far had little success in finding 'language' in non-human animals, applying the same methodologies to humans also fails to find any sign of 'language' in human communicative behaviour. Finally, while there have been a few attempts at direct communication or collaborative efforts between biological and linguistic fields, these articles are sometimes highly technical (and thus of limited accessibility to the target audience), and sometimes dismissively critical, thus discouraging further constructive exchanges between communities.…”
Section: Introductionmentioning
confidence: 99%